Mapping the Landscape of ‘No Poverty’ Research: A Bibliometric Study of Trends and Emerging Themes - Purwanto, Edi (Nur Science Institute, 2024)
In alignment with the United Nations' Sustainable Development Goals, this paper conducts a bibliometric analysis of “No Poverty” research to illuminate key trends, influential authors, and impactful topics. Despite global efforts, poverty remains pervasive, prompting the need for scholarly inquiry. Analyzing data from academic databases like Scopus, our study identifies a minimal global interest in “No Poverty” research, with only 17 publications over 37 years. However, a noticeable increase in publications since 2011 suggests a growing scholarly attention to the topic. Journal articles dominate the publication landscape, emphasizing their role in disseminating research findings. Diverse subject areas, including social sciences, environmental science, and business management, contribute to the interdisciplinary nature of poverty studies. The analysis also identifies thematic clusters focusing on socioeconomic interventions and ecological sustainability. While current research provides valuable insights, there's a call for innovative approaches and new research themes to address emerging challenges. Overall, this analysis underscores the multidimensional nature of “No Poverty” research and the importance of interdisciplinary collaboration in informing evidence-based policies toward poverty eradication and sustainable development goals.